Characterization of Affected Parameters in Laser-Treated Melisma - Kadhim Malik, Nidhal; Mahdi Al-Sultani, Methaq Mutar (Journal of Neonatal Surgery, 2025)
Melasma is a disorder in the regulation of balance mechanisms that control skin pigmentation, leading to excessive melanin production. It is an acquired disorder in melanin formation that results in skin hyperpigmentation. It always appears as symmetrical brown to grayish-black patches with irregular jagged edges, particularly in sun-exposed areas. Various methods are used to treat melasma, one of which is laser therapy with different wavelengths. In this study, the Spectra VRM III laser with a wavelength of 1064 nm was used. This laser reduces pigmentation by fragmenting the accumulated melanin pigment. Several factors influence melasma treatment, leading to an increase or decrease in the number of required sessions. Therefore, the objective of this study was to highlight the most important factors affecting melasma treatment. Among these factors are the melasma area and thermal diffusion length. A negative correlation was found between thermal diffusion length and melasma area: as the melasma area increases, the thermal diffusion length decreases, leading to an increased number of treatment sessions. Additionally, the melasma area negatively affects the melanocyte inhibition coefficient, resulting in a higher number of treatment sessions. Regarding the absorbed melanin pigment weight, it increases with the melasma area.